Moderate patient-prosthesis mismatch after valve replacement for severe aortic stenosis has no impact on short-term and long-term mortality. Issue 12 (1st May 2008) - Mascherbauer, J; Rosenhek, R; Fuchs, C; Pernicka, E; Klaar, U; Scholten, C; Heger, M; Wollenek, G; Maurer, G; Baumgartner, H
Abstract : Background: The importance of moderate patient-prosthesis mismatch (PPM) for the prognosis of patients who undergo aortic valve replacement is unclear. Methods: The presence of PPM was assessed in 361 consecutive patients undergoing valve replacement for isolated severe aortic stenosis and related to perioperative and postoperative mortality. Indexed effective orifice areas (EOAi) were estimated for each type and size of prosthesis. Results: Using the previously proposed cut-off of EOAi ⩽0.8 cm 2 /m 2, PPM was present in 54% of patients. Patients were followed for 4.1 (2.0) years. Survival tended to be slightly, but insignificantly, worse in the group with PPM (1-year, 3-year and 5-year survival 89%, 86% and 76% vs 92%, 88% and 82%; p = 0.21). However, patients with PPM were also older (p<0.0001), more often female (p<0.0001), more symptomatic (p = 0.001), more often had coronary artery disease (p = 0.04), triple vessel disease (p = 0.03) and hypertension (p = 0.01) and presented with a higher EuroSCORE (p<0.0001). By multivariate analysis only EuroSCORE and diabetes but not PPM were independent predictors of survival. Conclusions: Moderate PPM is a frequent finding after aortic valve replacement. In our patient population it had no impact on short-term and long-term survival. It may therefore not be justified to recommend complex surgical interventions to avoid moderate PPM in patients undergoing aortic valve replacement for isolated severe aortic stenosis.